2024
DOI: 10.1007/s00296-024-05541-4
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of dietary interventions in rheumatoid arthritis: can we improve patient conversations around food choices?

Prakriti Sharma,
Shannon Brown,
Elke M. Sokoya

Abstract: Rheumatoid arthritis (RA) is one of over 100 different types of autoimmune conditions. In RA, the cells of the immune system attack the tissue lining the joints, triggering inflammation. A large body of research suggests that the underlying trigger(s) of RA are unique to an individual. For example, increased risk of RA can be driven by smoking tobacco in one individual and mercury exposure in another. Due to the development of next-generation sequencing technology, the critical role of the microbiota in shapin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 94 publications
0
0
0
Order By: Relevance
“…Our study found no differences between the EAG and the low-carbohydrate group [ 47 ]. Also, we did not find benefits of other elimination diets, which, according to the authors of a recent review [ 48 ], are a powerful tool for reducing inflammation, including due to the effect on the microbiota. However, to date, they are not clearly stated in the guidelines and require predetermining levels of antibodies to dietary proteins.…”
Section: Discussionmentioning
confidence: 59%
“…Our study found no differences between the EAG and the low-carbohydrate group [ 47 ]. Also, we did not find benefits of other elimination diets, which, according to the authors of a recent review [ 48 ], are a powerful tool for reducing inflammation, including due to the effect on the microbiota. However, to date, they are not clearly stated in the guidelines and require predetermining levels of antibodies to dietary proteins.…”
Section: Discussionmentioning
confidence: 59%